2019
DOI: 10.1186/s13104-019-4380-3
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequences of Mycolicibacterium peregrinum isolated from a pig with lymphadenitis and from soil on the same Japanese pig farm

Abstract: Objectives Mycolicibacterium peregrinum , a rapidly growing mycobacterial species, can opportunistically infect humans and other animals. Although M. peregrinum infections in animals have been reported, the infection sources are unknown, as is information on its virulence and drug resistant genes, which limits our current understanding of this bacterium. To address this knowledge gap, we obtained draft genome sequences for two M. peregrinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Mycolicibacterium peregrinum was the most frequently isolated RGM from the different wildlife species-sika deer, wild boar, Japanese monkey, Japanese weasel, masked palm civet, and raccoon dog-which strongly suggested that wildlife may acquire Mycolicibacterium peregrinum from their environment. Studies conducted in Japan revealed that the draft genome sequence of Mycolicibacterium peregrinum isolated from a pig affected with lymphadenitis shares close identity with that of Mycolicibacterium peregrinum isolated from the soil of the pig's environment (Komatsu et al 2019). Moreover, the fact that Mycolicibacterium peregrinum was isolated from other animals (e.g., lion; Panthera leo), and from drinking water (Gcebe and Hlokwe 2017;Mohajeri et al 2017) indicates that Mycolicibacterium peregrinum can inhabit several environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycolicibacterium peregrinum was the most frequently isolated RGM from the different wildlife species-sika deer, wild boar, Japanese monkey, Japanese weasel, masked palm civet, and raccoon dog-which strongly suggested that wildlife may acquire Mycolicibacterium peregrinum from their environment. Studies conducted in Japan revealed that the draft genome sequence of Mycolicibacterium peregrinum isolated from a pig affected with lymphadenitis shares close identity with that of Mycolicibacterium peregrinum isolated from the soil of the pig's environment (Komatsu et al 2019). Moreover, the fact that Mycolicibacterium peregrinum was isolated from other animals (e.g., lion; Panthera leo), and from drinking water (Gcebe and Hlokwe 2017;Mohajeri et al 2017) indicates that Mycolicibacterium peregrinum can inhabit several environments.…”
Section: Discussionmentioning
confidence: 99%
“…To provide more information on the ecology and etiology of NTM, we previously presented the genome sequences of Mycolicibacter virginiensis, Mycolicibacter senuensis, and Mycobacterium colombiense isolated from the environment surrounding pigs in Japan (Ito et al 2018a, b). In addition, we analyzed the genome sequences of Mycolicibacterium peregrinum isolated from the lymph nodes of a pig and from the surrounding soil by in silico DNA-DNA hybridization, and the results showed that the two isolates were 100% identical (Komatsu et al 2019), implying circulation of NTM between the animal and the surrounding environment. Although NTM cases have been recorded in both humans and animals, the focus has been on humans more than on animals, especially wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the NCBI database, there is a bias as only genomes of defined species are associated with plasmids. Moreover, despite several reports of Mycolicibacterium genomes [15][16][17][18][19][20][21][22][23][24][25][26], these studies rarely survey plasmids among their contigs. Thus, only a few plasmids have been reported in this genus, mainly from unrecognized genomes [2,14,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This may contribute to their diversity and evolution or even to their success as opportunistic pathogens (33). Studies conducted in Japan suggest that livestock could acquire Mycolicibacterium peregrinum from their environment (34). Presence of Mycolicibacterium representatives containing a set of ARGs in the natural environment could be a reservoir of genes for potential development of resistance in pathogenic groups.…”
Section: Resultsmentioning
confidence: 99%